Probing masses of SZ-detected clusters using clustering signatures. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Tshililo, Israel R.; Cress, Catherine; February, Sean
Abstract: We investigate the clustering of clusters detected by Planck via the Sunyaev-Zeldovich (SZ) effect. The bias (the offset of the clustering relative to what is expected for dark matter) is then used to estimate the average mass of clusters in the sample, using mass-bias relations found in simulations. We also compare the clustering of Planck clusters with those detected in the Sloan Digital Sky Survey (SDSS) using the GMBCG method. Our results indicate that Planck clusters have a higher average mass than that inferred from their SZ signatures.